Bridge Condition Assessment and Prioritization using Bridge Management System in Kutai Timur Regency - Aco Wahyudi Efendi; Novia Safitri; Muh Yusuf; Irwan Faisal Luzan; Azan Zubran (Nusantara Civil Engineering Journal, 2025)
This study evaluates the condition of 215 bridges across 18 sub-districts in East Kutai Regency using a Bridge Management System (BMS). Primary data was collected through visual inspections, analyzing element-specific (foundation, substructure, superstructure, and deck) and overall condition ratings. The bridge inventory is predominantly timber construction (48.37%) and features mostly short spans, though critical long-span bridges exist. Results indicate most foundation, substructure, superstructure, and deck elements are in good condition (ratings 1-2). However, a significant percentage of elements show moderate to severe damage (ratings 3-5), with 1.86% of decks and superstructures in critical condition. A bridge prioritization model was developed based on condition ratings and urgency. Strategic recommendations include data-driven maintenance planning, efficient budget allocation, and enhancing human resource capacity and technology for sustainable bridge asset management, minimizing infrastructure failure risks